INVESTIGATION OF IMAGES FILTRATION METHODS IN COMPUTER SYSTEMS AND SPECIAL PURPOSE NETWORKS - MYRONIUK, Mykola; OPEN’KO, Pavlo; LARIN, Volodymyr; TOLKACHENKO, Yevhenii (Повітряна міць України, 2021)
It is known that human eyes are less sensitive to color, than to their brightness. In the RGB color space, all three components are considered equally important, and they are usually stored with the same resolution. However, you can display a color image more efficiently, separating the brightness from color information and presenting it with a higher resolution than color. RGB space is well suited for computer graphics, because it uses these three components for color formation. However, RGB space is not very effective when it comes to real images. The fact is that to save the color of an image, you need to know and store all three components of the RGB, and if one of them is missing, it will greatly distort the visual image representation. Also, when processing images in RGB space, it is not always convenient to perform any pixel conversion, because, in this case, it will be necessary to list all three values of the RGB component and write back. This greatly reduces the performance of various image processing algorithms.